Estabilidade, sob efeito de perturbacoes de uma classe de equacoes diferenciais funcionais neutras - Monteiro, Paulo Adao (1981)
The purpose of this work is to study stability properties of solutions of a neutral functional differential equation under perturbation by a class of functions. One of these stability properties is total stability, and another is integral stability. To investigate the behavior of perturbed equations, some kind of stability of a solution of the unperturbed equation has to be assumed. Recently the notion of stability in variation was introduced and a formula analogous to the variation of constants formula for a class of neutral functional differential equations was developed by A. Ventura. Assuming stability in variation and employing the variation of constants formula due to Ventura we prove that, for a class of neutral functional differential equations, stability in variation implies stability under perturbation by a class of functions